2008
DOI: 10.1111/j.1471-4159.2008.05538.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroids and GABAA receptor plasticity in the brain of the WAG/Rij rat, a model of absence epilepsy

Abstract: The role of neuroactive steroids and GABAA receptors in the generation of spontaneous spike‐and‐wave discharges (SWDs) was investigated in the WAG/Rij rat model of absence epilepsy. The plasma, cerebrocortical, and thalamic concentrations of the progesterone metabolite 3α‐hydroxy‐5α‐pregnan‐20‐one (3α,5α‐TH PROG) were increased in the WAG/Rij rat at 2 months of age compared with those in control (Wistar) rats. In contrast, the brain and peripheral levels of 3α,5α‐tetrahydrodeoxycorticosterone (3α,5α‐TH DOC) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 70 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…For instance, it was revealed that (i) Ino showed an anticonvulsant effect on quinolinic acid (QA)-induced seizures (Ganzella et al, 2011), (ii) Guo may decrease QAinduced seizures dose-dependently (Schmidt et al, 2000) and (iii) Urd decreased epileptic activity in the rat hippocampal kindling model (Zhao et al, 2008) and in a model of human absence epilepsy Wistar Albino Glaxo/Rijswijk (WAG/Rij) rats (Kova´cs et al, 2013b) suggesting the antiepileptic potential of non-Ado nucleosides. It is well known that GABAergic system (e.g., GABA A type of gamma-aminobutyric acid receptors: GABA A receptors), glutamatergic system (e.g., via glutamate-evoked excess hyperexcitability) and adenosinergic system (e.g., A 2A type of Ado receptors, A 2A receptors) are involved in the pathomechanisms of absence epilepsy (Snead, 1995;Coenen and Van Luijtelaar, 2003;Pisu et al, 2008;D'Alimonte et al, 2009). Thus, we hypothesized that (i) Ino and Urd may have effects on absence epilepsy through GABA A and Ado receptors (Skolnick et al, 1979;Kimura et al, 2001a;Hasko´et al, 2004;Kova´cs et al, 2015), (ii) Guo may change absence epileptic activity via the glutamatergic system De Oliveira et al, 2004;Schmidt et al, 2007;Kova´cs et al, 2015), (iii) Ino and Guo may modulate absence epilepsy through Ado receptors indirectly by their degradation to Ado or by stimulation of Ado release (Guo) (Zimmermann, 1996;Ciccarelli et al, 2000;Ipata, 2011;Kova´cs et al, 2015) and, theoretically, (iv) Guo and Urd may exert their effects on absence epileptic activity via own putative receptors (Kimura et al, 2001a(Kimura et al, , 2001bTraversa et al, 2003;Volpini et al, 2011;Kova´cs et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was revealed that (i) Ino showed an anticonvulsant effect on quinolinic acid (QA)-induced seizures (Ganzella et al, 2011), (ii) Guo may decrease QAinduced seizures dose-dependently (Schmidt et al, 2000) and (iii) Urd decreased epileptic activity in the rat hippocampal kindling model (Zhao et al, 2008) and in a model of human absence epilepsy Wistar Albino Glaxo/Rijswijk (WAG/Rij) rats (Kova´cs et al, 2013b) suggesting the antiepileptic potential of non-Ado nucleosides. It is well known that GABAergic system (e.g., GABA A type of gamma-aminobutyric acid receptors: GABA A receptors), glutamatergic system (e.g., via glutamate-evoked excess hyperexcitability) and adenosinergic system (e.g., A 2A type of Ado receptors, A 2A receptors) are involved in the pathomechanisms of absence epilepsy (Snead, 1995;Coenen and Van Luijtelaar, 2003;Pisu et al, 2008;D'Alimonte et al, 2009). Thus, we hypothesized that (i) Ino and Urd may have effects on absence epilepsy through GABA A and Ado receptors (Skolnick et al, 1979;Kimura et al, 2001a;Hasko´et al, 2004;Kova´cs et al, 2015), (ii) Guo may change absence epileptic activity via the glutamatergic system De Oliveira et al, 2004;Schmidt et al, 2007;Kova´cs et al, 2015), (iii) Ino and Guo may modulate absence epilepsy through Ado receptors indirectly by their degradation to Ado or by stimulation of Ado release (Guo) (Zimmermann, 1996;Ciccarelli et al, 2000;Ipata, 2011;Kova´cs et al, 2015) and, theoretically, (iv) Guo and Urd may exert their effects on absence epileptic activity via own putative receptors (Kimura et al, 2001a(Kimura et al, , 2001bTraversa et al, 2003;Volpini et al, 2011;Kova´cs et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Both α 4 and δ subunits are found in extrasynaptic GABA A receptors, where they facilitate tonic inhibition. Therefore, it has been hypothesized that the age-dependent increase in α 4 and δ subunits increases tonic inhibition in thalamic relay neurons, which then contributes to the age-dependent increase in SWDs (Pisu et al, 2008). GABAergic neurotransmission clearly plays a relevant role during SWDs; in WAG/Rij rats, this neurotransmitter system is functionally altered in several areas and this may depend on an altered subunit composition of GABA receptors.…”
Section: Gabamentioning
confidence: 99%
“…Decreased allopregnanolone and 3α,5α-TH-DOC in the cortex (Pisu et al, 2008) Increase in α 4 GABA A receptor subunit expression in some dorsal thalamic nuclei and an age-dependent increase in δ subunits…”
Section: Gabamentioning
confidence: 99%
“…However, in WAG/Rij rats confl icting results have been reported. An increase in the expression of α4 and δ subunits of the GABA A receptor was observed in the relay nuclei of adult epileptic WAG/Rij animals [ 70 ] whereas decreased immunoreactivity of α3 subunit of the GABA A receptor was reported at inhibitory synapses in the reticular nucleus of the thalamus [ 47 ].…”
Section: Gaba a Receptorsmentioning
confidence: 98%